Spatial effect towards malay reserve land development with the implementation of state structure plan / Muhammad Adli Abdul Jamil - Abdul Jamil, Muhammad Adli (2021)
In the development process that involved with the Malay Reserve Land (MRL), there are many obstacles such as multiple ownership issues on a land, weakness in term of land administration for MRL and lack of policy for the purpose of development at MRL area must be faced in order to obtain the land for the development process. Therefore, this study was conducted to investigate the spatial effect of Malay Reserve Land (MRL) area in the implementation of State Structure Plan. In order to achieve the aim, this study is arranged to reach the objectives as: - i) to investigate the current issues involved in development of Malay Reserve Land (MRL) area ii) to investigate the use of Kedah Structure Plan in state development planning iii) to analyse the spatial effect of Kota Setar and Pokok Sena MRL area with the implementation of Kedah Structure Plan. The study was carried out at the northern state of Peninsular Malaysia. For this study, the data of Malay Reserve Land area will overlap with the development planning area to construct a geospatial development planning for the MRL area. From this research, the finding is mostly the current land use at MRL area does not according to the development planning policy except for agriculture land that lies below the planning curve. Besides that, development policy also does not focus specifically on MRL development. Because of that, this study may help the local authority to keep up to date on the current development pace of the Malay Reserve Land. Besides, the area of MRL can be planned for the development according to the development policy. It is also to keep the awareness about the importance of Malay Reserved Land to be preserved in this country.